Dental fear in adolescents' transition to early adulthood - Jaakkola, Sirkka (Annales Universitatis Turkuensis D 1162, 2015)
The aims of the study were to assess the validity of a clinical dental fear question (Short Dental Fear Question, SDFQ) and an instrument measuring interaction between adolescents and dental staff (Patient Dental Staff Interaction Questionnaire, PDSIQ). Also, adolescents’ subjective perception of interaction with dental staff, the association with adolescents’ dental fear and sense of coherence as well as a multi-professional small-group intervention model for decreasing high dental fear were assessed. The study sample comprised Finnish adolescents in transition to early adulthood, aged 18–26 years (n = 777, n = 773, n = 5), except for a sample of 15-year-old adolescents (n = 27). Dental fear, sense of coherence (SOC) and the adolescents’ perceived interaction with dental staff were assessed with questionnaires. The principles of fear treatment such as gradual exposure, relaxation, encouragement and cornerstones of the reteaming method based on a solution-focused framework to maintain motivation and peer support were used to decrease fear in the intervention study. The SDFQ was found to be a valid dental fear instrument and the PDSIQ a valid interaction instrument with five factors of interaction retrieved: ‘kind atmosphere and mutual communication’, ‘roughness’, ‘insecurity’, ‘trust and safety’, and ‘shame and guilt’. Highly fearful young adults more often perceived their interaction with dental staff as negative, more often felt insecure and had a weaker sense of coherence compared to their peers with no to moderate dental fear. The results of the intervention study showed that young adults’ high dental fear decreased and their commitment to dental treatment increased. The SDFQ is clinically feasible and informative instrument in measuring dental fear. Knowledge of the level of fear enables dental staff to better consider an adolescent’s fear. Dental staff should be aware that a supportive interaction style, creating trust and safety, is especially beneficial for highly dentally fearful young adults. A weak SOC may affect young adults’ high dental fear in that they would not have enough tools to manage their fear. A multi-professional small therapeutic group seems to increase fearful young adults’ resources for confronting dental treatment.

Tutkimuksen tarkoituksena oli arvioida kliinisen hammashoitopelkomittarin (SDFQ) kuin myös nuoren ja suun terveydenhuollon henkilöstön välistä vuorovaikutusta mittaavan mittarin (PDSIQ) validiteettia, nuoren subjektiivista käsitystä suun terveydenhuollon henkilöstön kanssa käydystä vuorovaikutuksesta, nuoren hammashoitopelon ja koherenssintunteen välistä yhteyttä, ja moniammatillista pienryhmäinterventiomallia kovan hammashoitopelon vähentämisessä. Tutkimuksen havaintoaineisto muodostui pääosin aikuistuvista suomalaisnuorista iältään 18-26 vuotta (n = 777, n = 773, n = 5) lukuun ottamatta 15-vuotiaiden nuorten otosta (n = 27). Hammashoitopelkoa, koherenssintunnetta ja nuoren kokemaa vuorovaikutusta suun terveydenhuollon henkilöstön kanssa arvioitiin kyselyin. Moniammatillisessa pienryhmäinterventiossa käytettiin hammashoitopelon hoidon perusperiaatteita kuten asteittaista altistamista, rentoutusta, kannustusta sekä lisäksi ratkaisukeskeiseen viitekehykseen perustuvan muutosvalmennusprosessin kulmakiviä: motivaation ylläpitämistä sekä vertaistukea. SDFQ osoittautui validiksi hammashoitopelkomittariksi ja PDSIQ validiksi vuorovaikutusmittariksi, josta löytyi viisi eri vuorovaikutuksen osa-aluetta kuvaavaa faktoria: ’ystävällinen ilmapiiri ja vastavuoroinen viestintä’, ’karskius’, ’turvattomuus’, ’luottamus ja turvallisuus’ sekä ’häpeä ja syyllisyys’. Kovasti hammashoitoa pelkäävät nuoret kokivat vuorovaikutuksensa suun terveydenhuollon henkilöstön kanssa useammin kielteiseksi ja turvattomaksi verrattuna niihin nuoriin, joilla oli vähemmän tai ei lainkaan hammashoitopelkoa. Myös heikko koherenssintunne oli yleisempää kuin vahva kovasti pelkäävien nuorten keskuudessa. Interventiotutkimuksen tulosten mukaan nuorten aikuisten kova hammashoitopelko väheni ja heidän sitoutumisensa hammashoitoon lisääntyi. SDFQ on kliinisesti toimiva ja informatiivinen mittari hammashoitopelon mittaamisessa. Tieto pelon voimakkuudesta auttaa suun terveydenhuollon henkilöstöä ottamaan paremmin huomioon nuoren pelkoineen. Suun terveydenhuollon henkilöstön tulee pitää mielessään, että erityisesti kovasti pelkäävä nuori hyötyy kannustavasta, luottamusta ja turvallisuutta herättävästä vuorovaikutustyylistä. Heikko koherenssintunne saattaa vaikuttaa nuoren aikuisen kovaan hammashoitopelkoon siten, ettei hänellä oli tarpeeksi keinoja, kuinka selviytyä pelkonsa kanssa. Moniammatillinen terapeuttinen pienryhmä näyttää lisäävän nuoren aikuisen keinoja hänelle pelottavan hammashoidon kohtaamiseen